Correction: Nanoparticles of Cu2ZnSnS4 as performance enhancing additives for organic field-effect transistors. Issue 22 (20th May 2016) - Kevin, Punarja; Malik, Mohammad Azad; O'Brien, Paul; Cameron, Joseph; Taylor, Rupert G. D.; Findlay, Neil J.; Inigo, Anto R.; Skabara, Peter J.
Abstract : Correction for 'Nanoparticles of Cu2 ZnSnS4 as performance enhancing additives for organic field-effect transistors' by Punarja Kevin et al., J. Mater. Chem. C, 2016, DOI: ; Web:10.1039/c6tc01650b .